TEMPORAL COUPLING BETWEEN EXTERNAL AUDITORY INFORMATION AND THE PHASES OF WALKING - Mauerberg, E.; Adrian, M. (Perceptual Motor Skills, 1995)
The purpose of this study was to investigate the effects of an imposed external auditory constraint upon the temporal organization of walking. Ten subjects were videotaped walking normally (N) and with instructions to couple naturally, at mid-swing, or at toe-off to a metronome beat. Based upon an analysis of variance and post hoc Scheffe tests most temporal variables were not significantly different among conditions. The duration of swing phase was significantly different between natural coupling and toe-off. The deviation from the metronome beat was significantly different between the natural coupling and both mid-swing and toe-off. Subjects generally were not successful in achieving coupling during the latter conditions. Thigh and shank phase portraits were used to describe the system's organization to the external constraint.